Corrected QT interval in hospitalized patients with coronavirus disease 2019: Focus on drugs therapy. Issue 28 (16th July 2021) - Ding, Jiaxing; Liu, Wei; Guan, Hongquan; Feng, Yu; Bao, Yintu; Li, Huili; Wang, Xuehua; Zhou, Zihua; Chen, Zhijian
Abstract : Abstract: Corrected QT (QTc) interval prolongation has been associated with poor patient prognosis. In this study, we assessed the effects of different drugs and cardiac injury on QTc interval prolongation in patients with coronavirus disease 2019 (COVID-19). The study cohort consisted of 395 confirmed COVID-19 cases from the Wuhan Union Hospital West Campus. All hospitalized patients were treated with chloroquine/hydroxychloroquine (CQ/HCQ), lopinavir/ritonavir (LPV/r), quinolones, interferon, Arbidol, or Qingfei Paidu decoction (QPD) and received at least 1 electrocardiogram after drug administration. Fifty one (12.9%) patients exhibited QTc prolongation (QTc ≥ 470 ms). QTc interval prolongation was associated with COVID-19 severity and mortality (both P  < .001). Administration of CQ/HCQ (odds ratio [OR], 2.759; 95% confidence interval [CI], 1.318–5.775; P  = .007), LPV/r (OR, 2.342; 95% CI, 1.152–4.760; P  = .019), and quinolones (OR, 2.268; 95% CI, 1.171–4.392; P  = .015) increased the risk of QTc prolongation. In contrast, the administration of Arbidol, interferon, or QPD did not increase the risk of QTc prolongation. Notably, patients treated with QPD had a shorter QTc duration than those without QPD treatment (412.10 [384.39–433.77] vs 420.86 [388.19–459.58]; P  = .042). The QTc interval was positively correlated with the levels of cardiac biomarkers (creatine kinase-MB fraction [rho = 0.14, P  = .016], high-sensitivity troponin I [rho = .22, P  < .001], and B-type natriuretic peptide [rho = 0.27, P  < .001]). In conclusion, QTc prolongation was associated with COVID-19 severity and mortality. The risk of QTc prolongation was higher in patients receiving CQ/HCQ, LPV/r, and quinolones. QPD had less significant effects on QTc prolongation than other antiviral agents.